인삼 신품종의 뿌리부위별 진세노사이드 함량 및 패턴비교 - 안인옥(In-Ok Ahn); 이성식(Sung-Sik Lee); 이장호(Jang-Ho Lee); 이미자(Mi-Ja Lee); 조병구(Byung-Gu Jo) (Journal of ginseng research, 2008)
This study was carried out to evaluate the basic information on ginsenoside contents and pattern similarity in five cultivars of Panax ginseng C.A. Meyer. Among five cultivars the unit content and total content of ginsenosides were the highest in Gopoong cultivar as 18.9 mg/g and 596 mg/root, respectively. The unit content and total content of ginsenosides decreased in the order of Yunpoong, Gumpoong, Seonpoong and Chunpoong cultivar. Ginsenoside pattern similarity between tap root and lateral root was high as 0.95 but that between tap root and fine root was low as 0.72. Correlation of ginsenoside contents between tap root and lateral root exhibited the highest value as 0.843 and decreased in the order of main root, fine root, and rhizome. And the correlation value between unit content and total content of ginsenoside was very high as 0.933. 인삼의 부위별 진세노사이드 패턴 유사성과 상관관계를 알아보고자 본 시험을 수행하였다. 진세노사이드 단위함량과 총함량은 고풍이 각각 18.9 mg/g, 596 mg/g으로 가장 높았고 연풍, 금풍, 선풍이 뒤를 이었으며, 천풍은 각각 8.0 mg/g, 209.5 mg/g으로 고풍의 절반에도 미치지 못하였다. 부위별로 보면 뇌두의 진세노사이드 단위함량과 총함량은 연풍이 가장 높았으며, 동체와 지근 및 세근에서는 고풍이 높았다. 뿌리와 각 부위의 진세노사이드 패턴 유사성은 지근과 뇌두가 각기 0.95, 0.94로 높았으며 동체와 세근은 각기 0.78, 0.80으로 다소 낮았다. 지근에서 품종별 진세노사이드 패턴 유사성을 보면 천풍, 연풍, 고풍, 금풍이 각기 0.98, 0.98, 0.96, 0.98로 아주 높았으며, 선풍은 0.87로 다소 낮았다. 뿌리와 각 부 위의 진세노사이드 상관계수는 지근에서 0.843으로 가장 높았으며 동체, 세근, 뇌두 순으로 낮아졌다. 또한 단위함량과 총 함량의 상관계수는 0.933으로 매우 높게 나타났다.